If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 20 + -1p = 40 Solving 20 + -1p = 40 Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '-20' to each side of the equation. 20 + -20 + -1p = 40 + -20 Combine like terms: 20 + -20 = 0 0 + -1p = 40 + -20 -1p = 40 + -20 Combine like terms: 40 + -20 = 20 -1p = 20 Divide each side by '-1'. p = -20 Simplifying p = -20
| 7x^4+x=0 | | 3(7x+4)=6(x+2) | | -8-k=-25 | | 35x^2-3=22x | | (8x-41)+(9x+17)=180 | | r-7=58 | | X-1+5=-15+16x-7 | | 5-x+1=2 | | X=259 | | 26-2b=-8 | | x=5/2=10 | | y-0.7x=12 | | 15*3-25+10=x | | -4-7x=1-6x | | (5n-1)(n+7)=0 | | 8-2(4x+9)=6x-4(m-5) | | 15-z=45 | | 9x+17=8x-41 | | -4y+8=-8y-12 | | 6x-6=14x-14 | | -14-r-6r=r+8 | | 2210=r(34) | | 42=2+6 | | 9-4b=6-5b | | 6-4(5+3y)=0 | | 8-1/2(-m-1) | | M+6=2m+11 | | 7v-15+7v=7v+48 | | 23=32x-425 | | 1680=336t | | 5(9x+6)=45x-4 | | 0.5x=-70 |